Social Exclusion of Youth in Europe The Multifaceted Consequences of Labour Market Insecurity - Unt, Marge; Gebel, Michael; Bertolini, Sonia; Deliyanni-Kouimtzi, Vassiliki; Hofäcker, Dirk (Policy Press, 2021)
"EPDF and EPUB available Open Access under CC-BY-NC-ND licence. Policymakers throughout Europe are enacting policies to support youth labour market integration. However, many young people continue to face unemployment, job insecurity, and the subsequent consequences. Adopting a mixed-method and multilevel perspective, this book provides a comprehensive investigation into the multifaceted consequences of social exclusion. Drawing on rich pan-European comparative and quantitative data, and interviews with young people from across Europe, this text gives a platform to the unheard voices of young people. Contributors derive crucial new policy recommendations and offer fresh insights into areas including youth well-being, health, poverty, leaving the parental home, and qualifying for social security. "